THE EFFECT LEADER MEMBER EXCHANGE AND PSYHCHOLOGICAL EMPOWERMENT ON ORGANIZATIONAL IDENTIFICATION: THE CASE OF MUĞLA SITKI KOÇMAN UNIVERSITY (Third Sector Social Economic Review, 2022)
In today's world, where competition is getting faster, human resources have become an important key factor for organizations. Organizations need qualified employees in order to maintain their existence and to provide sustainable competition advantage. On the other hand, in order to ensure sustainable competition advantage, it is not enough to have only qualified employees, but at the same time, the employees must use all their knowledge and skills in business-related activities. This emerges when the employees adopts the goals of the organization as their own by displaying a positive attitude towards the organization. In this context, the identification of the employees with the organization emerges as an important issue in terms of providing the highest level of benefit to the organization. Employees who identify with their organization establish a bond between themselves and their organization, and work-related activities become more meaningful for them. In this context, the aim of this study is to find out the relationship between leader member exchange (LMX), psychological empowerment and organizational identification. The relationships between leader member exchange, psychological empowerment and organizational identification were conceptually examined and hypotheses created for this purpose were tested. The datas were obtained with survey technique The study group of the research consists of 298 academic and administrative staff in Muğla Sıtkı Koçman University. Factor, correlation and regression analyzes were applied to the data provided in the study. As a result of the research findings; It has been determined that there are significant and positive relationships between leader-member exchange and organizational identification, as well as between psychological empowerment and organizational identification.
Keywords: Leader-member exchange; psychological empowerment; organizational identification; Empowerment; Leadership.